Local lower extremity hyperkalemia during robotic prostatectomy: A case report - James Harvey Jones; Justin Wain (Urology Case Reports)
Robotic urologic surgery often requires patients to be placed in the steep Trendelenburg position with upper extremities tucked, limiting access for vascular lines and laboratory samples. A case of lower extremity hyperkalemia due to Trendelenburg positioning is presented. This case emphasizes that localized hyperkalemia, secondary to lower extremity hypoperfusion in the context of prolonged Trendelenburg positioning during robotic surgery, may not respond to systemic therapies, which could lead to systemic hyperkalemia upon return to the supine position.